Decentralization in Peru: Current situation, perspectives and some underlying questions - Monge Salgado, Carlos (2004)
On July 28, three years have passed since President Toledo announced that decentralization would be one of the central policies of his government and that in November 2022 -in parallel with the municipal elections scheduled for that date- elections would be held for the new regional authorities.